Modelling of human expert decision making in reservoir operation - Wan Ishak, Wan Hussain; Ku-Mahamud, Ku Ruhana; Md Norwawi, Norita (Penerbit UTM Press, 2015)
Reservoir is one of the structural approaches for flood mitigation and water supply.During heavy raining season, reservoir operator has to determine fast and accurate decision in order to maintain both reservoir and downstream river water level. In contrast to less rainfall season, the reservoir needs to impound water for the water supply purposes.This study is aimed to model human expert decision making specifically on reservoir water release decision.Reservoir water release decision is crucial as reservoir serve multi purposes.The reservoir water release decision pattern that comprises of upstream rainfall and current reservoir water level has been form using sliding window technique.The computational intelligence method called artificial neural network was used to model the decision making.